1988
DOI: 10.1113/jphysiol.1988.sp016932
|View full text |Cite
|
Sign up to set email alerts
|

Free‐calcium and force transients during depolarization and pharmacomechanical coupling in guinea‐pig smooth muscle.

Abstract: SUMMARY1. Fura2 was loaded by permeation and hydrolysis of the acetoxymethyl ester into smooth muscle cells of intact thin sheets of the longitudinal layer of the small intestine of the guinea-pig, to record Ca21 transients during contraction.2. Cytoplasmic Ca2+ ([Ca2+]i) was monitored by computing the ratio of the fluorescence signal excited at 340 and 380 nm wavelengths. The dye loading and the exposure to UV light required for the experiments had no significant effect on the contractile parameters observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(107 citation statements)
references
References 63 publications
13
94
0
Order By: Relevance
“…The common response to K+ was a monophasic increase in [Ca 2+]i (R340/380) consisting of a rapid spike and quasi-exponential decline, which was accompanied by a biphasic contraction: an ini tial phasic component followed by varying de grees of partial relaxation (data not shown). These results are in agreement with the find ings of Himpens and Somlyo (19). The peak amplitudes of both [Ca 2+]i (R340/380) and mus cle tension induced by the test agonist were compared with those by 70 mM K+ and ex pressed as a percentage of those by 70 mM K+ Both [Ca 2+]i (R340/380) and muscle tension, expressed as a percentage of those induced by 70 mM K , were increased by all the agonists in a concentration-dependent manner (Figs.…”
Section: Resultssupporting
confidence: 82%
“…The common response to K+ was a monophasic increase in [Ca 2+]i (R340/380) consisting of a rapid spike and quasi-exponential decline, which was accompanied by a biphasic contraction: an ini tial phasic component followed by varying de grees of partial relaxation (data not shown). These results are in agreement with the find ings of Himpens and Somlyo (19). The peak amplitudes of both [Ca 2+]i (R340/380) and mus cle tension induced by the test agonist were compared with those by 70 mM K+ and ex pressed as a percentage of those by 70 mM K+ Both [Ca 2+]i (R340/380) and muscle tension, expressed as a percentage of those induced by 70 mM K , were increased by all the agonists in a concentration-dependent manner (Figs.…”
Section: Resultssupporting
confidence: 82%
“…Loading the strips with fura-2 did not alter the time courses and the maximum levels of tension development during 118 mm Kt-depolarization, thereby suggesting that tissue damage by possible acidification of the cells due to formaldehyde released on acetoxymethyl-ester hydrolysis did not occur (Tsien et al, 1982;Rink & Pozzan, 1985 (Figure 8). This suggests that receptor-mediated stimulation increased Ca2+-sensitivity of the contractile apparatus (Morgan & Morgan, 1984;Bruschi et al, 1988;Himpens & Somlyo, 1988;Rembold & Murphy, 1988;Sato et al, 1988). In addition, the [Ca2 t]i-tension relationship of the Ca2 '-induced contraction during depolarization was similar to the pCa-tension relationship noted with skinned fibres of the porcine coronary artery and of others (Saida & Nonomura, 1978;Kuriyama et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Since Himpens and Somlyo [9] suggested that extracellular hyperosmotic pressure resulted in leakage of fura2 from the cytosol, we used isosmotic 60 mM KCl (I-60 K + ) instead of H-65 K + in this experiment. The fluorescence ratio was expressed as a percentage by assuming the values at rest in normal PSS to be 0% and those at 10 min after addition of I-60 K + to be 100%.…”
Section: Muscle Preparations and Tension Measurementmentioning
confidence: 99%